A study of Chitosan and c‐di‐GMP as mucosal adjuvants for intranasal influenza H5N1 vaccine. Issue 6 (21st November 2012) - Svindland, Signe C.; Pedersen, Gabriel K.; Pathirana, Rishi D.; Bredholt, Geir; Nøstbakken, Jane K.; Jul‐Larsen, Åsne; Guzmán, Carlos A.; Montomoli, Emanuele; Lapini, Giulia; Piccirella, Simona; Jabbal‐Gill, Inderjit; Hinchcliffe, Michael; et al.
<x xml:space="preserve">Abstract</x> Please cite this paper as: Svindland et al. (2012) A study of Chitosan and c‐di‐GMP as mucosal adjuvants for intranasal influenza H5N1 vaccine. Influenza and Other Respiratory Viruses 10.1111/irv.12056000(000), 000–000. Background Highly pathogenic avian influenza A/H5N1 virus remains a potential pandemic threat, and it is essential to continue vaccine development against this subtype. A local mucosal immune response in the upper respiratory tract may stop influenza transmission. It is therefore important to develop effective intranasal pandemic influenza vaccines that induce mucosal immunity at the site of viral entry. Objectives We evaluated the humoral and cellular immune responses of two promising mucosal adjuvants (Chitosan and c‐di‐GMP) for intranasal influenza H5N1 vaccine in a murine model. Furthermore, we evaluated the concept of co‐adjuvanting an experimental adjuvant (c‐di‐GMP) with chitosan. Methods BALB/c mice were intranasally immunised with two doses of subunit NIBRG‐14 (H5N1) vaccine (7·5, 1·5 or 0·3 μg haemagglutinin (HA) adjuvanted with chitosan (CSN), c‐di‐GMP or both adjuvants. Results All adjuvant formulations improved the serum and local antibody responses, with the highest responses observed in the 7·5 μg HA CSN and c‐di‐GMP‐adjuvanted groups. The c‐di‐GMP provided dose sparing with protective single radial haemolysis (SRH), and haemagglutination inhibition (HI) antibody responses found in the 0·3 μg HA group. CSN elicited a Th2 response, whereas c‐di‐GMP induced higher frequencies of virus‐specific CD4+ T cells producing one or more Th1 cytokines (IFN‐γ+, IL‐2+, TNF‐α+). A combination of the two adjuvants demonstrated effectiveness at 7·5 μg HA and triggered a more balanced Th cytokine profile. Conclusion These data show that combining adjuvants can modulate the Th response and in combination with ongoing studies of adjuvanted intranasal vaccines will dictate the way forward for optimal mucosal influenza vaccines.